RETRACTED: The Strategy Detection on Information Security in Corporate Organizations on Crucial Asset - Yakubu Ajiji Makeri (JOIV : International Journal on Informatics Visualization, 2020)
Following a rigorous, carefully concerns and considered review of the article published in JOIV : International Journal on Informatics Visualization to article entitled â€œThe Strategy Detection on Information Security in Corporate Organizations on Crucial Assetâ€ Vol 4, No 1, pp. 35-39, March 2020, DOI: http://dx.doi.org/10.30630/joiv.4.1.280This paper has been found to be in violation of the JOIV : International Journal on Informatics Visualization Publication principles and has been retracted.The article contained redundant material, the editor investigated and found that the paper published inAl-Kalbani, A., Deng, H., Kam, B., & Zhang, X. (2016). Investigating the impact of institutional pressures on information security compliance in organizations [Conference paper]. In ACIS proceedings (pp. 1-12). RMIT Research Repository. https://core.ac.uk/download/pdf/83608347.pdf.Â A. AlKalbani, H. Deng, B. Kam, and X. Zhang, â€œInformation Security Compliance in Organizations: An Institutional Perspective,â€ Data and Information Management, vol. 1, no. 2, pp. 104â€“114, Dec. 2017, doi: 10.1515/dim-2017-0006.The document and its content has been removed from JOIV : International Journal on Informatics Visualization, and reasonable effort should be made to remove all references to this article.